German exports to the euro area - Sabine Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
The growth of the German economy intrinsically depends on the development of German exports to the euro area, which is by far the biggest market for German products. The paper estimates a structural equation for the export demand from the EMU member countries, which is suitable for both simulations and short-term forecasts. However, the equation systematically underestimates the export demand for data from 1999 onwards, indicating that German exports have greatly benefited from the introduction of the European Monetary Union–a special effect, that is not considered in the structural equation.
Keywords: C52; C22; F47; 330; Export Demand; Income and Price Elasticities; Intra-EMU Trade; Error Correction Model; Export; Nachfrage; Europäische Wirtschafts- und Währungsunion; Schätzung; EU-Binnenhandel; Deutschland